Direct analysis of volatile fatty acids in marine sediment porewater by two‐dimensional ion chromatography‐mass spectrometry. (7th July 2014) - Glombitza, Clemens; Pedersen, Jeanette; Røy, Hans; Jørgensen, Bo Barker
<x xml:space="preserve">Abstract</x> Volatile fatty acids (VFAs) are key intermediates in the microbial food web. However, the analysis of low concentrations of VFAs in marine porewater is hampered by interference from high concentrations of inorganic ions. Published methods often use sample pretreatment, including distillation or derivatization, to overcome this problem. This is not only labor intensive but also increases the risk of contamination. We have developed an analytical procedure that enables the direct quantification of several VFAs (formate, acetate, propionate, butyrate, valerate, pyruvate, and lactate) in marine porewater by two‐dimensional ion chromatography‐mass spectrometry (2D IC‐MS). The first chromatographic dimension is used to separate the VFAs from the inorganic ions whereas the second dimension separates the individual VFAs. Quantification and identification are achieved by online mass spectrometry in selected ion monitoring mode. No sample pretreatment is required and statistically determined detection limits are below 25 ppb (µg L−1). The method can also be used without the online coupling to a mass spectrometer. In the latter case, quantification of the VFAs can be done by the conductivity detector signal of the second dimension with the limitation that lactate cannot be quantified due to signal interference with an unidentified peak and pyruvate and valerate have slightly higher detection limits (<100 ppb).